Services for children and specialized organization for disabled persons and Roma in Belgrade - Nikolić Jasmina (Temida, 2007)
This paper presents the results of the survey on services for children and organizations specialized for disabled persons and Roma in Belgrade, with special emphasis on programs relevant for crime victims. This survey was conducted during 2006 and 2007 by Victimology Society of Serbia. In introduction, the author gives a short review of research methodology. In the next three parts of the paper, the author presents results of the survey on services for children, disabled persons and Roma in Belgrade, with special emphasize on specific fields of work of each organization. Finally, in conclusion, the author summarizes the data, analyzing them in connection to the current activities of VDS info and victim support service, and gives recommendations for possible solutions of further development of the Service related to the mentioned categories of victims. .